Speaking naturally : communication skills in American English - Tillitt, Bruce; Bruder, Mary Newton. 1939- (Cambridge [Cambridgeshire] ; New York : Cambridge University Press, 1985)
The Student's Book focuses on a language function$1 (Bsuch as requesting information, thanking, complimenting, and inviting$1 (Bwhile readings explain the cultural "rules" students need to know to communicate naturally and effectively. Structured exercises, as well as freer role plays, often involve pairs or small groups and encourage interaction in the classroom.s
TOC
English
Keywords: English language -- Textbooks for foreign speakers; English language -- Spoken English -- United States -- Problems, exercises, etc; Communication -- Problems, exercises, etc; Speech acts (Linguistics)